Cross‐cultural adaptation of the Hamilton axial spondyloarthritis questionnaire and development of a Chinese version in a multi‐ethnic Asian population. (27th June 2019) - Xiang, Ling; Teo, Edmund Pek Siang; Low, Andrea Hsiu Ling; Leung, Ying Ying; Fong, Warren; Xin, Xiaohui; Gandhi, Mihir; Kwan, Yu Heng; Uy, Elenore J. B.; Hamilton, Louise; Thumboo, Julian
Abstract: Objective: To cross‐culturally adapt the Hamilton axial spondyloarthritis (axial SpA) screening questionnaire and develop a Chinese version for use in a multi‐ethnic Asian population in Singapore. Methods: Consenting participants newly referred from primary care to a rheumatology specialist outpatient clinic for evaluation of possible axial SpA were studied. The original axial SpA questionnaire was revised based on inputs from cognitive debriefing interviews (CDIs) and discussions with an expert panel of rheumatologists and the developer. Forward and back translations of the adapted English version were also reviewed by the expert panel and the developer. The common translation produced was tested in CDIs with Chinese‐speaking participants. Adapted English and Chinese versions were pilot‐tested in a separate group of similar participants. Results: Participants were recruited for English (n = 25) and Chinese CDIs (n = 15, relatively older and less frequently presented with axial SpA symptoms), respectively. Alternative terms and explanatory notes were added to difficult medical terms to improve the understandability of the adapted English version. English medical terms were retained in the Chinese version. Pilot‐testing of the adapted axial SpA questionnaire was performed on 116 participants, all of whom reported ease of comprehension with both adapted versions. Only one participant was diagnosed with axial SpA, who also scored positive on the adapted axial SpA questionnaire. Conclusion: The adapted axial SpA questionnaire demonstrated good sensitivity in the pilot‐testing and appears to be a promising tool for facilitating early identification of axial SpA cases in the multi‐ethnic Asian population.